ISSUES OF STRENGTHENING COOPERATION RELATIONS BETWEEN REGIONAL FINANCIAL INSTITUTIONS AND UZBEKISTAN (Academicia Globe: Inderscience Research, 2025)
This article analyzes the topic of strengthening cooperation between regional financial institutions and our country. Among the regional financial institutions, the Asian Development Bank (ADB) has planned to implement several projects for Uzbekistan in the coming years. One of the major projects is the Uzbekistan railway electrification project, aimed at electrifying approximately 600 kilometers of railway lines in the country. This project will reduce our country's dependence on diesel fuel and increase the efficiency and reliability of the railway system. The total value of the project is 241 million dollars, with the ADB credit amounting to 189 million dollars. The implementation period for this project is set from 2022 to 2027. The main task of such funds is to support an acceptable level of debt in cases of pressure on payment balances and state budgets. The presented topic has been analyzed based on statistical data, and conclusions have been provided.